Recent Advances in Multi-Dimensional Vibration Mitigation Materials and Devices - Xu, Zhao-Dong; Chen, Zheng-Han; Huang, Xing-Huai; Zhou, Chen-Yu; Hu, Zhong-Wei; Yang, Qi-Hang; Gai, Pan-Pan (Frontiers in Materials, 2019)
Harmful vibrations can cause many engineering problems, such as disasters of civil engineering structures, failure of precision equipment, and out of order of some spacecraft components. On most situations, the vibrations are usually three dimensional excitations. Therefore, research on multi-dimensional vibration control became a world-wide hotspot in engineering. This article presents a comprehensive assessment of recent developments of multi-dimensional vibration mitigation devices and the material applied in such devices. The vibration mitigation materials mainly include the passive vibration mitigation materials and smart vibration mitigation materials. Subsequently, the vibration mitigation devices in civil engineering, mechanical engineering and aerospace engineering are reviewed and commented respectively. Above all, the multi-dimensional vibration mitigation devices and materials, are found to be effective for reducing multi-dimensional vibrations. However, enhancing the mitigation performance of the devices in each direction, including improving the mitigation capability of material, is still a challenging issue.